Lower Mantle Seismicity Following the 2015 Mw 7.9 Bonin Islands Deep‐Focus Earthquake. Issue 13 (7th July 2021) - Kiser, Eric; Kehoe, Haiyang; Chen, Min; Hughes, Amanda
Abstract: Deep‐focus earthquakes provide insight into how subducting slabs deform over a range of spatial and temporal scales as they descend into the mantle. This study uses a 4D source imaging approach to determine centroid locations of the 2015 Mw 7.9 Bonin Islands deep‐focus earthquake and its aftershock sequence. Imaged sources of the mainshock show a complex rupture, but one that is compatible with a sub‐horizontal rupture plane. Previously undetected early aftershocks are imaged down to depths of approximately 750 km and represent the first reported earthquakes that initiate in the lower mantle. These events and a previously reported group of shallower distal aftershocks occur at the lower and upper boundaries of an imaged slab segment that deforms as it penetrates into the lower mantle. We hypothesize that mainshock failure allowed gravitational settling of the slab segment to occur which produced the distal aftershock sequences. Plain Language Summary: The causes of earthquakes below depths of approximately 60 km inside the Earth have been debated for nearly a century. This study reports on the first detected earthquakes with source locations in the lower mantle. These observations provide new insights into the mechanisms that can produce earthquakes deep inside the Earth. Key Points: A 4D back‐projection method is used to image the 2015 Mw 7.9 Bonin Islands deep‐focus earthquake and its aftershock sequence Early aftershocks detected down to ∼750 km depth are the first reported events that initiate in the lower mantle Distal aftershocks are hypothesized to occur at the top and bottom boundaries of a settling slab segment in response to the mainshock